Upscaling Organizational Performance through Reward System in the Nigeria Private Sector - Stella Esogbuziem Nnabuife; Kifordu Anyibuofu Anthony; Ofili Peter Nkeonyeasua (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
The study examined the impact of reward system on organizational performance in the Nigeria Private Sector. The specific objectives are to: determine the impact of performance recognition on organizational performance and examine the impact of compensation policy on organizational performance. The cross-sectional survey research design was employed in this study. The population of this study consists of the management and staff of the selected private firms, First Bank Plc, Konga Group, MTN Nigeria, UBA Group, Total Energies and BUA Cement. The sample size of three hundred and sixty-seven was obtained using the Taro Yamane formula. A stratifie d sampling technique was used to determine the number of participants per organisation. The data were analyzed using regression analysis as analytical tools to test the hypotheses. Findings revealed that there is a positive significant impact of performance recognition on organizational performance; (0.039< 0.05). There is a positive significant impact of compensation policy on organizational performance (0.002, p<0.05). The study concluded that employee reward systems are important and should be of interest to both management and staff in the private sector organisations. The study recommends that, the management of private sector organisations devote resources for the development and implementation of effective reward system to produce the desired results.